The helix-loop-helix transcriptional regulator Id4 is required for terminal differentiation of luminal epithelial cells in the prostate - Hewa Bostanthirige, Dhanushka (Oncoscience, 2021)
Inhibitor of differentiation 4 (Id4), a member of the helix-loop-helix family of transcriptional regulators has emerged as a tumor suppressor in prostate cancer. In this study we investigated the effect of loss of Id4 (Id4-/-) on mouse prostate development. Histological analysis was performed on prostates from 25 days, 3 months and 6 months old Id4-/- mice. Expression of Amacr, Ck8, Ck18, Fkbp51, Fkbp52, androgen receptor, Pten, sca-1 and Nkx3.1 was investigated by immunohistochemistry. Results were compared to the prostates from Nkx3.1-/- mice. Id4-/- mice had smaller prostates with fewer and smaller tubules. Subtle PIN like lesions were observed at 6mo. Decreased Nkx3.1 and Pten and increased stem cell marker sca-1, PIN marker Amacr and basal cell marker p63 was observed at all ages. Persistent Ck8 and Ck18 expression suggested that loss of Id4 results in epithelial commitment but not terminal differentiation in spite of active Ar. Loss of Id4 attenuates normal prostate development and promotes hyperplasia/ dysplasia with PIN like lesions. The results suggest that loss of Id4 maintains stem cell phenotype of “luminal committed basal cells”, identifying a unique prostate developmental pathway regulated by Id4.